Delayed and disordered development of articulation and phonology between four and seven years. (June 2018) - Dodd, Barbara; Ttofari-Eecen, Kyriaki; Brommeyer, Katherine; Ng, Kelly; Reilly, Sheena; Morgan, Angela
Some children's speech impairment resolves spontaneously. Others have persistent problems affecting academic and social development. Identifying early markers that reliably predict long-term outcome would allow better prioritization for preschool intervention. This article evaluates the significance of different types of speech errors, made by 93 four-year-olds in a longitudinal population cohort study, for performance at seven years. At four years, the non-age appropriate speech errors made on standardized assessments were categorized as: phonologically delayed (error patterns typical of younger children); or, some errors atypical of normal development, including consistent errors (e.g. word initial consonant deletion), inconsistent pronunciations of the same word, or lateral distortion of /s, z/). Delayed children, some with occasional interdental /s, z/ articulation errors, were more likely to resolve (67%) than those making atypical errors (35%) by seven years. Qualitative analyses indicated that children making few atypical errors were more likely to resolve, irrespective of total number of errors or whether they received intervention. The findings' theoretical implications relate to deficits underlying phonological disorders. Clinical implications concern assessment measures and prioritization for intervention.